Leaf structure and cytochemical investigation of secretory tissues in Inula viscosa - Nikolakaki, A.; Christodoulakis, N.S. (Botanical Journal of the Linnean Society, 2004)
Leaves of Inula viscosa have been used in medicine from ancient times. Structures or cells with secreting activity were localized and a spectrum of products was histochemically identified within them. Leaf extracts were investigated with gas chromatography - mass spectrometry (GC-MS) and thin-layer chromatography (TLC). Calluses produced from leaf-cell cultures were also subjected to histochemical reagents and tested with GC-MS and TLC to investigate their secreting ability compared with that in leaves. Little-differentiated callus cells are synthetically active and produce, as do its leaf cells, numerous polar compounds that could be of pharmaceutical interest. © 2004 The Linnean Society of London.
Keywords: Anti-fungal agents; Asteraceae; Compositae; Dittrichia viscosa; Inula; leaf morphology; medicinal plant; Pharmaceutical compounds; Secondary metabolites; Thin-layer chromatography; Tissue culture